2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7319421
|View full text |Cite
|
Sign up to set email alerts
|

A study on cortico-muscular coupling in finger motions for exoskeleton assisted neuro-rehabilitation

Abstract: In this paper our objective is to analyze the cortico-muscular coupling for hand finger motion and its possible use in the control of an exoskeleton based neurorehabilitation system for stroke sufferers. Cortical activity alone is often not sufficient to reliably control a device such as an exoskeleton and hence, our focus is to ascertain and analyze the connectivity between the motor cortex and forearm muscles, controlling the fingers, in terms of coherence between electroencephalogram (EEG) and electromyogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 17 publications
(14 reference statements)
0
29
0
Order By: Relevance
“…µ= [8][9][10][11][12] Hz, β= [16][17][18][19][20][21][22][23][24] Hz). These two frequency ranges have been chosen empirically as they provide stable frequency response for Event-Related-Desynchronization or Event-Related-Synchronization (ERD/ERS) [43].…”
Section: E Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…µ= [8][9][10][11][12] Hz, β= [16][17][18][19][20][21][22][23][24] Hz). These two frequency ranges have been chosen empirically as they provide stable frequency response for Event-Related-Desynchronization or Event-Related-Synchronization (ERD/ERS) [43].…”
Section: E Methodsmentioning
confidence: 99%
“…The strong correlation between EEG signals and mental tasks has led to many user centric applications such as virtual spellers for the communication [7], functional electrical stimulation (FES) based neuro-prosthesis for tetraplegics [4], hand exoskeleton control [8], [9], [10], [11] and telepresence for personal assistance [12]. In spite of the seemingly bright prospect of the BCI technology, there are some practical challenges regarding the robustness, accuracy, and information transfer rate (ITR) of such systems [13], [14], [15].…”
mentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t multiple trials, the single trial based estimation of CMC may not be sufficiently accurate to correctly trigger contingent neurofeedback. CMC needs longer epochs for having good frequency resolution, which is difficult to accommodate in a single-trial based neurofeedback generation as it would include a larger delay in the system [39,40,41]. This is primarily due to the inter-trial inconsistency of the CMC caused by the presence of non-stationary changes in the EEG data.…”
Section: Page 6 Of 27mentioning
confidence: 99%
“…This is primarily due to the inter-trial inconsistency of the CMC caused by the presence of non-stationary changes in the EEG data. One of the major concerns is the reduction in maximum coherence value in case of stroke patients and its dynamic shift in frequency across different time segments [41,42]. Other pitfalls related to CMC includes lower information content, estimation vs. frequency resolution issues, and lower signal-to-noise ratio (SNR), especially for slow finger motions involving lower muscle mass.…”
Section: Page 6 Of 27mentioning
confidence: 99%
“…A final list with 30 studies was identified as eligible for qualitative review. Among the 30 studies, 11 [60][61][62][63][64][65][66][67][68][69][70] were involved in testing the BCI-hand robot system on chronic and subacute stroke patients ( [60,65] are RCTs) while the rest involved testing on healthy participants [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89].…”
Section: Figure 1 Study Selection Flowchartmentioning
confidence: 99%